Analisis Ekonometrika Pengaruh Lingkungan Sosial Terhadap Preferensi Karir Mahasiswa - Diah Ayu Pratama Putri; Nimas Ayu Lailasari; Nur Fathanah; Isnaini Khoirunnisa; Angga Pratama; Gustina Masitoh (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to determine the extent to which the social environment influences the tendency of students' career choices. The approach used is quantitative, with the analysis method in the form of multiple linear regression. A total of 150 active students from Nurul Huda University, East OKU acted as respondents in this study. Data collection was carried out through the distribution of closed questionnaires designed with a Likert scale, covering several main indicators such as the influence of family, friendship environment, and the role of educational institutions. The results of the analysis showed that the three aspects of the social environment had a significant influence on students' career preferences, with the influence of family factors as the most dominant. The conclusion of this study states that students' career choices are not only influenced by internal motivation, but also determined by the social environment in which they interact. Therefore, active involvement from family, educational institutions, and the surrounding environment is very important in supporting students' career direction optimally.